Market-Based Approaches for Managing the Asian Environment: A Review - Herath Gunatilake; Franklin D. De Guzman (Asian Development Bank (ADB), 2008)
This paper identifies inadequate effort to use market-based approaches, among others, as a reason for limited progress in arresting continuing environmental degradation in the Asia and Pacific region. Quoting examples, the paper asserts that markets can be created for ecosystem protection and provision of ecosystem services under innovative regulatory mechanisms; and that use of marketbased approaches can reduce the dependency on unsustainable financing for environmental management. The paper also briefly discusses the role of governments, donors, and other stakeholders in creating the enabling policy and institutional framework for introducing market-based approaches.
hdl:11540/1784
Keywords: 330; Umweltökonomik; Umweltpolitik; Asien